OP0031 Risk Factors for Malignancies Synchronous To The Onset of Systemic Sclerosis in Patients Positive for Anti- RNA Polymerase III Antibodies: A Eustar Multicentre Study. (15th July 2016) - Lazzaroni, M.G.; Cavazzana, I.; Colombo, E.; Distler, O.; Dobrota, R.; Hernandez, J.; Hesselstrand, R.; Czirjak, L.; Varju, C.; Nagy, G.; Smith, V.; Caramaschi, P.; et al.
Abstract : Background: Patients with anti-RNA polymerase III antibodies (anti-RNAP) have an increased risk of malignancies synchronous to the onset of Systemic Sclerosis (SSc). In a multicentre EUSTAR case-control study, however, only moderate odd ratio was observed (OR 3.85, 95%CI 1.3–10.9), except than for breast cancer (OR 20.2, 95%CI 1.4–355) (1). Defining clinical and demographic features characteristic of anti-RNAP+ SSc patients who suffer from simultaneous malignancy would be useful to individuate risk factors who can guide the clinicians in every-day practice to screen anti-RNAP+ SSc patients for cancer. Objectives: To individuate risk factors for malignancies synchronous to the onset of SSc in anti-RNAP+ patients. Methods: EUSTAR centers were asked to participate to this study, providing data on malignancy history of their anti-RNAP+ patients in a dedicated form. Results: Among 158 anti-RNAP+ SSc patients collected from 13 EUSTAR centers, 14 cases of malignancies synchronous to the onset of SSc were identified. When compared with the other 144 anti-RNAP+ patients, patients with synchronous malignancies had an older mean age at SSc onset (65.3 yrs (SD 10.0) vs 49.3 (SD13.3); p<0.001) and an increased proportion of diffuse cutaneous subset (96% vs 56%; p:0.008; OR: 10.5 95%CI 1.33–82.6). A trend for increased proportion of males was also observed (43% vs 21%; p:0.06). In particular, the risk of non-breast cancer synchronous with SSc was greatly higher in male than in female patients (43% vs. 0.8%; p<0.001; OR 95.2 95%CI 10.2–890). Conclusions: Anti-RNAP+ SSc patients of older age, and with diffuse cutaneous subset, are particularly at risk for malignancies synchronous to the onset of SSc. The risk of malignancies other than breast cancers is greatly increased in male patients. These risk factors may help in the screening for cancer in these patients. References: M.G. Lazzaroni et al. Anti-RNA Polymerase III Antibodies in Patients with Systemic Sclerosis: A Eustar Multicenter Collaborative Study. Ann Rheum Dis 2015;74:Suppl 2 88 doi:10.1136/annrheumdis-2015-eular.1728 Disclosure of Interest: None declared